2013
DOI: 10.6007/ijarbss/v3-i11/351
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Marketing Strategies Alignment on Supply Chain and Organizational Performance (Case Study: Entekhab Industrial Group)

Abstract: The purpose of this study is to evaluate the effect of marketing strategies alignment on supply chain and organizational performance in the Entekhab industrial group. The purpose of this study is functional -practical and the nature and the method of it is descriptive -survey and is of correlation type. The population of this study includes managers at various levels in the Entakhab industrial group in 2012 and statistical sample were 159 who were selected by simple random sampling. In this study, a questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…According to the results obtained from the test of the research model, it was concluded that supply chain capabilities have a significant and positive impact on operational and financial performance of the companies in the food industry. This result is in line with the findings of Day et al [6], Yu et al [30], Neupane et al [35,36], Hassan et al [11], Chi and Gursoy [26], Mahboubi [27], Dalvi et al [28], and Hosseini and Sheikhi [14]. Likewise, operational performance had a positive impact on financial performance of the food companies.…”
Section: Hypothesissupporting
confidence: 89%
See 1 more Smart Citation
“…According to the results obtained from the test of the research model, it was concluded that supply chain capabilities have a significant and positive impact on operational and financial performance of the companies in the food industry. This result is in line with the findings of Day et al [6], Yu et al [30], Neupane et al [35,36], Hassan et al [11], Chi and Gursoy [26], Mahboubi [27], Dalvi et al [28], and Hosseini and Sheikhi [14]. Likewise, operational performance had a positive impact on financial performance of the food companies.…”
Section: Hypothesissupporting
confidence: 89%
“…Mahboubi [27] conducted a research to investigate knowledge management capabilities, functions of supply chain management, and performance. The population of the study consisted of senior executives of manufacturing firms in Rasht industrial city.…”
Section: Conceptual Model and Hypothesesmentioning
confidence: 99%